Trends and transitions in ledipasvir studies: A bibliometric assessment of a groundbreaking hepatitis C virus treatment - Alshalla, Kauthar; Al-Rasheed, Mohammed; Mahmoud, Maryam; Azhari, Alaa; kandeel, Mahmoud (International Journal of Innovative Research and Scientific Studies, 2025)
This study aimed to conduct a comprehensive bibliometric analysis of global research on ledipasvir from 2014 to May 2025, focusing on trends in research output, citation impact, authorship patterns, and thematic evolution. A bibliometric analysis was performed using 419 scientific articles from 199 sources indexed in Scopus. Data were extracted based on publication year, authorship, citations, keywords, and institutional affiliations. Visualization tools such as VOSviewer and Bibliometrix were employed to analyze co-authorship networks, keyword co-occurrence, and thematic trends. Inclusion criteria prioritized peer-reviewed English articles with complete bibliographic metadata. The analysis revealed a peak in publication output in 2018 (92 articles), followed by a gradual decline. The United States, Egypt, and Japan emerged as leading contributors, with Gilead Sciences and academic institutions like Cairo University playing pivotal roles. High citation rates (average of 39.57 citations per document) underscored the drug’s ongoing relevance. Keyword analysis highlighted a shift from early clinical and pharmacokinetic studies to topics such as adherence, liver transplantation, and COVID-19 implications. International collaboration was robust, with 21.48% of publications involving multi-country teams. Ledipasvir research has evolved significantly, reflecting its foundational role in HCV treatment. Despite declining publication numbers, the drug’s scientific impact remains strong, driven by international collaboration and diverse thematic exploration. Future research should focus on comparative efficacy, long-term outcomes, and resistance mechanisms to further inform clinical practice.